Pemasaran Tas Purun Berbasis Web - Yuda Perwira; Wira Apriani; Fiqri Irhami; Kicky Maulana (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
In this digital era, business people must be creative and innovative in marketing their products to be able to survive against competitors and get good profits, one of which is to use information technology to transact or introduce their products. Nasti Purun is a housing business in the Perbaungan area that produces purun into bags. , hats and other products made from purun, the purpose of this service is to create a website to be able to transact online between nasti purun and consumers and create a digital catalog so that it can be easily accessed by customers without having to come to a location and can reach a wider market again, so that businesses can develop and create jobs for local residents.